Lay-Up Shoot Skills of Old-School Club Players: The Clout of Agility, Balance, and Coordination Ankles - Kasmad, Muhammad Rachmat; Ermanto, Helmiyana; Hudain, Muh. Adnan; AS, Hasbunallah; Sudiadharma, Sudiadharma (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study falls into the path analysis research category, employing the path analysis method for data analysis. The research subjects were Makassar Old School players. The population comprises all Old School Makassar players, with a sample size of 30. We used descriptive analysis as a data analysis technique, testing hypothesis requirements with the SPSS 25.00 program at a significance level of 95%, or 0.05. The research results show that: (1) agility has a significant direct influence on the layup shooting of old school Makassar players by 26.1%, with a significant level of 0.038 < α0.05. (2) The research also reveals a significant direct influence of balance on the lay-up shoot of old-school Makassar players. School Makassar is 80.5%, with a significance level of 0.000 < α0.05. (3) There is a significant direct influence of ankle coordination on the layup shot of old-school Makassar players by 20.3%, with a significant level of 0.031 < α0.05. (4) There is a significant direct influence of agility on the ankle coordination of Old School Makassar players at 80.7%, with a significance level of 0.000 < α0.05. (5) There is a significant direct influence of balance on the ankle coordination of Old School Makassar players at 26.3%, with a significant level of 0.038 < α0.05. (6) There is a significant direct influence of agility on lay-up shoot skills through Old School Makassar players' ankle coordination of 16.3%, with a significance level of 0.000 < α0.05. (7) There is a significant direct influence of balance on lay-up shoot skills through Old School Makassar players' ankle coordination of 5.3%, with a significance level of 0.000 < α0.05.